Preliminary Evidence for the Cognitive Model of Auditory Verbal Hallucinations in Youth With Borderline Personality Disorder - Cavelti, Marialuisa; Thompson, Katherine; Hulbert, Carol; Betts, Jennifer; Jackson, Henry; Francey, Shona; Chanen, Andrew (Frontiers in Psychiatry, 2019)
Objectives. This is the first study to explore cognitive, emotional, and behavioral responses to voices in youth with borderline personality disorder (BPD) compared with those with schizophrenia spectrum disorder (SZ), and to examine if negative appraisals of voices predict depression and anxiety across the groups. Methods. The sample comprised 43 outpatients, aged 15-25 years, who reported AVH and were diagnosed with either DSM-5 BPD or SZ. Data were collected using the Psychotic Symptom Rating Scales, the Beliefs About Voices Questionnaire-Revised, the Voice Rank Scale, and the Depression Anxiety Stress Scale. Results. Youth with BPD did not differ from youth with SZ in beliefs about the benevolence or malevolence of voices. Youth with BPD appraised their voices as more omnipotent and of higher social rank in relation to themselves, compared with youth with SZ. In both diagnostic groups, beliefs about malevolence and omnipotence of voices were correlated with more resistance towards voices, and beliefs about benevolence with more engagement with voices. In addition, perceiving the voices as being of higher social rank than oneself and negative voice content were both independent predictors of depression, irrespective of diagnostic group. In contrast, negative appraisals of voices did not predict anxiety after adjusting for negative voice content. Conclusions. This study replicated the link between negative appraisals of voices and depression that has been found in adults with SZ in a mixed diagnostic youth sample. It, thus, provides preliminary evidence that the cognitive model of AVH can be applied to understanding and treating voices in youth with BPD.